2009
DOI: 10.1590/s1679-87592009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and decoration preferences of the epialtidae crab Acanthonyx scutiforms

Abstract: A B S T R A C TStudies on the feeding preferences of marine herbivores are very important for our better understanding of the biology and the ecological role of these organisms. Members of the family Epialtidae are usually herbivores that mask themselves with pieces of seaweed and other materials to avoid predation. In order to better understand the mechanisms of food and decorating choices of the decorator crab Acanthonyx scutiformis, two multiple-choice feeding assays were performed using fresh seaweeds and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Several marine invertebrates prefer algae with low seasonal variation (Paine and Vadas 1969). This fact was particularly observed in the spider crab Mycrophyris bicornutus (Kilar and Lou 1984) and has been suggested to account for the algal preferences of Notomithrax ursus (Woods and McLay 1994) and Acanthonyx scutiformis (Vasconcelos et al 2009). Martin et al (2013) reported a low seasonal variation of Sphacelariales biomass in Bahía Bustamante.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several marine invertebrates prefer algae with low seasonal variation (Paine and Vadas 1969). This fact was particularly observed in the spider crab Mycrophyris bicornutus (Kilar and Lou 1984) and has been suggested to account for the algal preferences of Notomithrax ursus (Woods and McLay 1994) and Acanthonyx scutiformis (Vasconcelos et al 2009). Martin et al (2013) reported a low seasonal variation of Sphacelariales biomass in Bahía Bustamante.…”
Section: Discussionmentioning
confidence: 93%
“…However, small gastropods, polychaetes, isopods and amphipods are also found in some Epialtidae species studied (Woods and McLay 1994, Stachowicz and Hay 1999, Paiva Barros et al 2008, Vasconcelos et al 2009). By contrast, L. pentagona in Bahía Bustamante shows a specialized diet.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the patterns verified for L. variegatus, crude extracts from specimens of P. brasiliense from Enseada do Forno and Praia Rasa had no significant effect on feeding by the crab A. scutiformis (Figure 3). In fact, this crab is a generalist feeder, but it exhibits some preference by the chemically-defended P. brasiliense and also uses this macroalga as decoration and probably protection against predation (Vasconcelos et al, 2009). In fact, this is a typical mechanism exhibited by small and more specialised marine organisms that live associated to and consume the chemically defended host to minimise predation (Hay, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…A number of Codium species, including C. intertextum are known to possess dimethylsulfoniopropionate (DMSP), a substance that can decrease the activity of generalist feeders over their thalli (Van Alstyne and Puglisi, 2007). Similarly, P. brasiliense possesses halogenated monoterpenes (Vasconcelos et al, 2010) and Laurencia species produces elatol (Pereira et al, 2003), both of which prevent herbivore action towards these algae (Pereira et al, 2003;Vasconcelos et al, 2009).…”
Section: Discussionmentioning
confidence: 99%